Pengaruh Kepemimpinan Kepala Madrasah dan Budaya Organisasi terhadap Kinerja Guru di Madrasah Aliyah Negeri Kota Medan - Ardansyah, Muhammad; Purba, Cawir Rufinus; Abrar, Ragil Wahyuda (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2025)
This study aims to analyze the influence of principal leadership and organizational culture on teacher performance at Madrasah Aliyah Negeri (MAN) in Medan City. An associative quantitative approach was applied, involving a sample of 184 teachers selected through proportional random sampling. Data were collected using a closed-ended questionnaire with a four-point Likert scale, developed based on theoretical indicators of each variable. Before analysis, validity tests, reliability tests, and classical assumption tests were conducted to ensure the quality of the data. The results of multiple linear regression analysis revealed that principal leadership (beta coefficient = 0.491; p < 0.05) and organizational culture (beta coefficient = 0.204; p < 0.05) each had a significant partial effect on teacher performance. Simultaneously, both variables also showed a significant combined effect (F value = 26.290; p < 0.05), with a coefficient of determination (R²) of 0.324. This means the model explains 32.4% of the variation in teacher performance, while the remaining 67.6% is influenced by other factors such as personal motivation, academic qualifications, and availability of learning facilities. These findings highlight the vital role of principal leadership as the main driver, as well as the contribution of organizational culture in creating a collaborative work climate that supports teacher performance. It is hoped that this research can serve as a reference for policy development aimed at improving educational quality, especially in state madrasahs located in large cities like Medan.